Odpowiedzi

  • megu
  • Rozwiązujący
2010-03-10T21:18:45+01:00
A) 15x
b) 4a
c) 0
d) 11b
e) 8x
f) 1y
g) -7z
h) 4,5x + 1
i) -4,5t
62 4 62
2010-03-10T21:19:29+01:00
A) 6x + 4x + 5x = 15x
b) 2a + 5a - 3a = 4a
c) 3b + 2b -5b = 0b
d) 3b + 8b = 11b
e) 17x - 9x = 8x
f) 4y + (-3y) - 4y -3y = y
g) 8z - 15z = -7z
h) 6x - 2x + 1½x = 5½x
i) 5t - 7t + ( - 2,5t ) = 5t - 7t - 2,5t = -4,5t
78 4 78
2010-03-10T21:21:31+01:00
A) 6x + 4x + 5x=
= 15x

b) 2a + 5a - 3a=
= 4a

c) 3b + 2b -5b=
= 0

d) 3b + 8b=
= 11b

e) 17x - 9x=
= 8x

f) 4y + (-3y)=
= 4y-3y=
= y

g) 8z - 15z=
= -7z

h) 6x - 2x + 1 i jedna druga x
1 i 1/2 x -> 1,5x
6x-2x+1,5x=
= 5,5x (5 i 1/2x)

i) 5t - 7t + ( - 2,5t )=
= 5t-7t-2,5t=
= -4,5t
48 3 48